Contribution of prejudiced clustering education system in developing horizontal and vertical mismatch in job market: quality of employees in banking sector - Alam, Gazi Mahabubul; Roslan, Samsilah (Emerald Group Publishing, 2021)
Purpose: Education system supplies the required manpower in order to ensure the national prosperity. A salient link between education and business sector is a prerequisite to cater economically productive manpower. Economic and social development supplements each other that can only be ensured via a functional education system. A dysfunction education system created by a biased clustering policy develops a greater horizontal and vertical mismatch with the job market in many developing nations. This mismatch dents the quality of business management that halts the national prosperity. Therefore, the role of education has become questionable. This research aims to bridge between education and business sectors. Design/methodology/approach: Given the differentiated nature of research questions, multiple techniques are used to collect the data. However, this research bears the norms of qualitative method. Both secondary and primary data are used. While, secondary data are collected by the banks, Bangladesh Bureau of Educational Information and Statistics (BANBEIS) and by the University Grants Commission (UGC), primary data are collected through interviews. Document review and data collected through personal communication with members of staff of sampled banks and institutes of HE also supplements. Data were collected from six commercial banks and from the Central Bank. Findings: Findings suggest that clustering system favours science graduates by depriving business counterpart, which creates an atmosphere of educational disparity. This disparity affects the symbiotic and reciprocal relationship that exists amongst different provisions (i.e. secondaryand tertiary) of education. Favoured clustering system further contributes for a larger “horizontal educational mismatch” with job market. Therefore, science graduates occupy the places in the banks where business graduates should ideally be employed. Being a dysfunction system, education fails to support substantially for social and economic developments. Originality/value: A few studies are conducted in the area of HE in Bangladesh but none covers the issue of impact of clustering system of education in secondary provision on HE and job market. Graduates' performance in carrying out the jobs is seen as the most important element for the business management. This study has suggested a unique way forward which would be able to reduce the mismatch between education system and job market, enabling a substantial business management process. Considering this, the paper is first on its kind.